The solid-state structures of organic salts formed by calix[4]arene dihydroxyphosphonic acid with nucleic bases cations: adeninium, cytosinium, guaninium and uracilium. Issue 5 (3rd June 2018) - Shkurenko, Aleksander; Lazar, Adina N.; Collard, Dominique; Navaza, Alda; Kim, Beomjoon; Tauran, Yannick; Perret, Florent; Journet-Gautier, Catherine; Coleman, Anthony W.; Suwinska, Kinga
Abstract: Calix[4]arene dihydroxyphosphonic acid has been demonstrated to possess an interesting range of biological properties, including atypical anti-cancer activity. The robustness of calix[4]arene dihydroxyphosphonic acid and its ubiquitous dimeric motif offers perspectives for pre-defined solid state complexation with small molecules. In the current article we describe co-crystals (organic salts) of calix[4]arene dihydroxyphosphonic acid with four nucleic base cations: adeninium, cytosinium, guaninium and uracilium. A number of characteristic interactions between the components in the four co-crystals are pointed out also using the Hirshfeld surface analysis. All the four co-crystals are based on layers of calix[4]arene dimers, alternating with layers of nucleic acid molecules. Two of the reported crystal structures (cytosinium and guaninium) are 1D channel-type structures, while the two others (adeninium and uracilium) represent 2D channel-type structures. In three out of four reported structures, interactions between the cations of nucleic bases are present generating 1D chains of cations. A constant motif is that the nucleic base is present in a type of cavity formed by one aromatic ring and a phosphonic acid moiety. Abstract :